Influence of development phase on production characteristics of lucerne in Zetsko-Bjelopavlicki valley's agroecological conditions - Dubljević Radisav; Mitrović Dragoljub (Agroznanje, 2011)
In this document there are results of two years research on influence of development phase on production characteristics of lucerne, with determing of the optimal harvest time as the main objective. Reserches are conducted in Zetsko-Bjelopavlicka valley's agroecological conditions, using irrigation (irrigation norm 250 - 3 0 0 1/m'2 and irrigation rate 50 1/m'2) and three variants of mowing (four times, five times and six times mowing system).Mowings are conducted at the following phenological stages: boot stage, beginning of flowering and full flowering (seeding pods), observing the occurrence and development of buds on the crown roots. Based on these results we can conclude that the intensity of utilization, in reference to number of mowing and phenological stages when mowing is conducted has very significant influence on production properties, primarily on the yield and nutritive value of the lucerne fodder.